The Effect of Test Presentation on Children With Autism Spectrum Disorders and Neurotypical Peers. - Alt, Mary; Moreno, Melanie Humphrey (Language, Speech & Hearing Services in Schools, 2012)
Purpose: The purpose of this experiment was to determine if there is alternate forms reliability for paper- and computer-administered standardized vocabulary tests. Another purpose was to determine whether the behavioral ratings of children with autism spectrum disorders (ASDs) would improve during the computer-administered testing sessions secondary to a decreased need for social interaction. Method: Thirty-six school-age children (half with ASDs, half neurotypical [NT]) took 2 versions (i.e., paper vs. computer) of the Expressive One-Word Picture Vocabulary Test (EOWPVT-2000; Brownell, 2000a) and the Receptive One-Word Picture Vocabulary Test (ROWPVT-2000; Brownell, 2000b). Order of presentation was counterbalanced across participants. Test sessions were videotaped, and randomly selected 1-min intervals were rated for behaviors. Standardized test scores and behavior ratings were compared for equivalence across the test presentation methods. Results: Standard scores for both versions of the tests were not significantly different for both groups of participants. There were no differences in behavioral ratings between the two methods of test presentation. Conclusion: Alternate forms reliability was found, thus expanding the options for testing for school-age populations. The use of computers had no effect on the behaviors of the children with ASDs. The ramifications of this finding for assessment and intervention for children with ASDs are discussed.